Local attribute-similarity weighting regression algorithm for interpolating soil property valuesLocal attribute-similarity weighting regression algorithm for interpolating soil property values - Jiaogen, Zhou; Daming, Dong; Yuyuan, Li (International Journal of Agricultural and Biological Engineering, 2017)
Existing spatial interpolation methods estimate the property values of an unmeasured point with observations of its closest points based on spatial distance (SD). However, considering that properties of the neighbors spatially close to the unmeasured point may not be similar, the estimation of properties at the unmeasured one may not be accurate. The present study proposed a local attribute-similarity weighted regression (LASWR) algorithm, which characterized the similarity among spatial points based on non-spatial attributes (NSA) better than on SD. The real soil datasets were used in the validation. Mean absolute error (MAE) and root mean square error (RMSE) were used to compare the performance of LASWR with inverse distance weighting (IDW), ordinary kriging (OK) and geographically weighted regression (GWR). Cross-validation showed that LASWR generally resulted in more accurate predictions than IDW and OK and produced a finer-grained characterization of the spatial relationships between SOC and environmental variables relative to GWR. The present research results suggest that LASWR can play a vital role in improving prediction accuracy and characterizing the influence patterns of environmental variables on response variable. Keywords: attribute similarity, geographically weighted regression, local regression, spatial interpolation DOI: 10.25165/j.ijabe.20171005.2209 Citation: Zhou J G, Dong D M, Li Y Y. Local attribute-similarity weighting regression algorithm for interpolating soil property values. Int J Agric & Biol Eng, 2017; 10(5): 95–103.